1999
DOI: 10.1212/wnl.52.2.392
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a very large trinucleotide repeat in a patient with juvenile Huntington’s disease

Abstract: A patient with juvenile Huntington's disease (HD) of probable maternal inheritance is reported. The expanded IT-15 allele was only detected with the use of modified PCR and Southern transfer techniques, which showed a CAG trinucleotide repeat expansion of approximately 250 repeats-the largest CAG expansion reported within the huntingtin gene. This case emphasizes the need for communication between the diagnostic laboratory and the clinician to define the molecular genetics of unusual cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 9 publications
6
91
0
2
Order By: Relevance
“…10 The longest CAG repeat found by Seneca et al 18 was the repeat with 214 CAG copies. Nance et al 19 reported an individual with juvenile-onset HD who had 250 CAG repeats. This patient had a maternal history of HD, but the mother's allele could not be determined because a DNA sample was not available.…”
Section: Discussionmentioning
confidence: 99%
“…10 The longest CAG repeat found by Seneca et al 18 was the repeat with 214 CAG copies. Nance et al 19 reported an individual with juvenile-onset HD who had 250 CAG repeats. This patient had a maternal history of HD, but the mother's allele could not be determined because a DNA sample was not available.…”
Section: Discussionmentioning
confidence: 99%
“…Although the upper limit of detection is not known, alleles carrying ~115 CAG repeats have been amplified by PCRbased methods, 26 whereas alleles carrying more than ~125 CAG repeats appear to be refractory to reproducible amplification. 15 Polymorphisms surrounding or within the CAG tract have been identified and have a collective frequency of >1% in patients referred for HD testing.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…14 The largest expanded HD allele detected to date carries ~250 CAG repeats in a patient with juvenile-onset disease. 15 Mosaicism. Mosaicism attributable to both mitotic and meiotic instability has been described in brain and sperm, and it appears to be more pronounced in juvenile-onset cases of HD associated with larger CAG expansions.…”
mentioning
confidence: 99%
“…The largest reported intergenerational expansion is þ160 repeats wherein a father with 54 repeats had a child with 214 repeats [Seneca et al, 2004]. Nance et al [1999] reported a juvenile-onset HD case of 250 repeats in a patient with a maternal history of HD; however, a DNA sample was not available to confirm the mother's allele size. Laccone and Christian [2000] described two sisters with HD in which they inherited maternal expansions of þ21 and þ30 repeats.…”
Section: Introductionmentioning
confidence: 99%